2014
DOI: 10.1521/aeap.2014.26.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Contextual Factors Related to Delayed HIV Diagnosis Among Men Who Have Sex With Men

Abstract: Delayed HIV diagnosis among men who have sex with men (MSM) in the United States continues to be a significant personal and public health issue. Using qualitative and quantitative data from 75 recently tested, HIV-seropositive MSM (38 delayed and 37 non-delayed testers) we sought to further elucidate potential personal and contextual factors that may contribute to delayed HIV diagnosis among MSM. Our findings indicate MSM who experience multiple life stressors, whether personal or contextual, have an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…As with HIV incidence, data suggest an even higher burden of late diagnoses among racial/ethnic minority MSM secondary to HIV stigma and limited social support. [98][99][100] Breaking chains of HIV transmission necessitates not just coverage of HIV testing, but the diagnosis of people during the acute and early infection stages followed by effective and sustained intervention. Thus, universal HIV treatment approaches are challenged in terms of optimising clinical outcomes and eliminating onward HIV transmission in the context of late diagnoses.…”
Section: -69mentioning
confidence: 99%
“…As with HIV incidence, data suggest an even higher burden of late diagnoses among racial/ethnic minority MSM secondary to HIV stigma and limited social support. [98][99][100] Breaking chains of HIV transmission necessitates not just coverage of HIV testing, but the diagnosis of people during the acute and early infection stages followed by effective and sustained intervention. Thus, universal HIV treatment approaches are challenged in terms of optimising clinical outcomes and eliminating onward HIV transmission in the context of late diagnoses.…”
Section: -69mentioning
confidence: 99%
“…The following demographic factors have been associated with HIV testing behavior among MSM: older age, [6, 918]; education level [16, 19, 20]; and socio-economic status (SES) [11, 16, 21]. MSM’s high-risk sexual behavior has also been found to be either negatively associated with timely HIV testing [11, 15, 20, 22], or to be unassociated with it [10, 12, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Seeking sexual partners on the Internet has been negatively associated with HIV testing among MSM [19, 20]. As for psychosocial factors, perceptions of risk have been positively associated with HIV testing [6, 15, 18, 23, 24], as has self-efficacy to engage in protective behaviors [21]. More use of information regarding HIV/AIDS has also been associated with greater HIV testing intentions among YMSM [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who, out of necessity, availed themselves of $40 or a place to stay from their social support alters may be experiencing a level of chaos in their lives that makes it difficult to access testing on a regular basis. Consistent with this idea, a recent study found that experiencing a greater number of life stressors, such as homelessness, was associated with delayed HIV testing among a sample of men who have sex with men (Nelson et al, 2014). Coping with chronic daily stressors and hassles may decrease motivation or ability to get tested every six months.…”
Section: Discussionmentioning
confidence: 82%